Epidemiological Traits and Seasonal Variation of Henoch-Schonlein Purpura (HSP) in Children - Kalar, Musleh Uddin; Musaelyan, Arine; Nikolaevna, Vitkovskaya Elizaveta; Mansoor, Farah; Azaaibi, M.; Mathew, Schwan (International Journal of Innovative Research in Medical Science, 2018)
Background: HSP is typically a disease of children between the ages of 3 and 10 years. Although adult cases have been described, 50% of all cases occur at or before the age of 5 years. Males are affected twice as often as females. In North America, Caucasians have the highest prevalence, and African Americans have the lowest prevalence. Although the cause of HSP is unknown, it commonly follows an upper respiratory tract infection. As a result, the disease is more common in winters. Objectives: To determine the prevalence of Henoch-Schonlein purpura (HSP) in children. To determine the seasonal variation of Henoch-Schonlein purpura (HSP) in children. Materials and Methods: This was a cross sectional study conducted at Jinnah Postgraduate Medical Center & Karachi Medical & Dental College. Children (<17 yr of age) diagnosed with HSP were included on the basis of non-probability convenient sampling. The diagnosis of HSP was based on the standard defined by the American College of Rheumatology. The sample size calculation was done using the World Health Organization, Geneva software where α=5%, 1-Beta=80, Po=0.15, Pa=0.20, sample size=342. Continuous variables like age and number of patients admitted at various time of year were presented as mean ± standard deviation. Categorical variables, gender and age (<14, >14 years) were presented as proportions. Results: Mean age of children with HSP was 11 ± 1.5 years. Majority of the children 43.6% were <14 years of age in 2017 and 51.2% in 2018. The annual prevalence of HSP from 2017 till 2018 increased to 9.2%. The frequency of hospitalization also increased, 2017: 40%; 2018: 59%. Males were 71% and females were 28%. Male to female ratio was 2.0. Males >10 years were 29% and females >10 years were 70% (p<0.05) Table1. Number of cases increased from 8-12 years of age and were less frequent in <8 years and >14 years of age. Majority, 20% of cases were of 10 years age. HSP occur all year round with a high prevalence in the winter season. Number of patients increased from 2% in June and July to 58% from November till February. Conclusion: The overall prevalence of HSP was 19.5 per 1000 affecting children of 9 to 11 years in winters.